The Political Economy of Tourism in Brazil (2003-2016): a “Positive” yet still Neoliberal Agenda? - Thiago Duarte Pimentel; Mariana Pereira Chaves Pimentel; Marcela Costa Bifano de Oliveira; Dominic Lapointe (Via@)
Recently, tourism has gained significant relevance, as nation-states view it as a development alternative due to the constraints and resource limitations they face. In this conceptual paper, we develop a comprehensive analytical framework to examine the political economy of tourism (PET), aiming to integrate and go beyond the partial analyses conducted so far. To illustrate our model, we used secondary data from the period of the Workers’ Party governments in Brazil (Luís Inácio Lula da Silva, 2003–2010, and Dilma Rousseff, 2011–2016), as previous studies indicate that this period was marked by a notable increase and qualitative shift in the tourism sector in Brazilian history. Our findings reveal that tourism in Brazil underwent a profound transformation, both quantitatively and qualitatively, during the analyzed period. According to our interpretative framework, we argue that this transformation stemmed from the positive alignment of macrosocial factors (such as the absence of crisis, coupled with international economic expansion driven by demand and a progressive national strategy) with the national agenda, creating favorable conditions for the expansion and diversification of the tourism sector in Brazil. However, for this “positive agenda” to be successful, it remains rooted in a neoliberal framework, characterized by massive, inbound, and concentrated tourism. These are pre-conditions with which one must contend, even if considering the possibility of reorienting the activity toward a more socially redistributive agenda.